Toxicity and effects of combined agrochemical in Scaptotrigona bipunctata bees - Diniz, T. O.; Pereira, N. C.; Silva, B. G.; Pizzaia, W. C. S.; Oliveira, F. G. M.; Gigliolli, A. A. S.; Takasusuki, M. C. C. R. (Scientific Electronic Archives, 2020)
The commercial insecticide Fastac Duo is a combined insecticide, widely used in different crops, acting on insects, affecting both pests and pollinators, such as bees. In this study, the effects of sublethal concentrations of Fastac Duo in stingless bees Scaptotrigona bipunctata were evaluated. Worker forager bees were exposed to the insecticide and histochemical and morphological analyses were conducted after 24, 48 and 72 h of ingestion. Brain analysis of S. bipunctata revealed changes in the chromatin condensing state according to exposure time and insecticide concentration when compared to the control group. Morphological changes were observed in the midgut in all concentrations and exposure times, which may interfere in several physiological processes. In conclusion, although the concentrations used in the study did not cause high mortality, it induced changes in the internal morphology that can lead to changes in bee activity.